Social computing and social media : communication and social communities : 11th International Conference, SCSM 2019, held as part of the 21st HCI International Conference, HCII 2019, Orlando, FL, USA, July 26-31, 2019, Proceedings.: communication and social communities : 11th International Conference, SCSM 2019, held as part of the 21st HCI International Conference, HCII 2019, Orlando, FL, USA, July 26-31, 2019, Proceedings. Part II (2019) - Unknown
No abstract available